2019
DOI: 10.1002/lno.11144
|View full text |Cite
|
Sign up to set email alerts
|

Environmental drivers of mixotrophs in boreal lakes

Abstract: Mixotrophy is increasingly recognized as an important trophic pathway among phytoplankton, yet its underlying drivers remain largely unknown and unexplored. Here, we present a study utilizing 69 lake samplings in boreal Quebec, Canada, identifying variables driving the success of phytoplankton that have a capacity for mixotrophy and pointing to the underlying mechanisms. We found that the success of mixotrophs (% of total biomass) was positively influenced by both colored dissolved organic matter (cDOM) and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 87 publications
2
33
0
Order By: Relevance
“…We found that brown algae and cryptophytes were most sensitive to zooplankton as a driver of their vertical distribution, in support of our hypothesis H2 that highly edible taxa would be most sensitive to potential top-down control by zooplankton grazing (Holm et al 1983;Brett et al 2000Brett et al , 2006Hansson et al 2019). The brown algae spectral group, likely comprised of predominantly chrysophytes in our study lakes (Fig.…”
Section: Nutritious Taxa Are Sensitive To Top-down Controlsupporting
confidence: 88%
“…We found that brown algae and cryptophytes were most sensitive to zooplankton as a driver of their vertical distribution, in support of our hypothesis H2 that highly edible taxa would be most sensitive to potential top-down control by zooplankton grazing (Holm et al 1983;Brett et al 2000Brett et al , 2006Hansson et al 2019). The brown algae spectral group, likely comprised of predominantly chrysophytes in our study lakes (Fig.…”
Section: Nutritious Taxa Are Sensitive To Top-down Controlsupporting
confidence: 88%
“…The lower biodiversity of Chrysophyta with microscopy can be related to preservation and magnification issues because these algal cells preserve poorly in Lugol and accurate taxonomic assignment depends on details only visible with scanning electron microscopy (Wujek & O’Kelly, 1992). In many oligotrophic and cold freshwater ecosystems where the mixotrophic nature of Chrysophyta (Rothhaupt 1996) is an advantage (Hansson, Grossart, del Giorgio, St‐Gelais, & Beisner, 2019) a high diversity of Chrysophyta‐related OTUs has been observed along with a high total abundance of sequences (e.g. 25–50% Charvet et al, 2012; 25–60% Lara et al, 2015; 37% Ortiz‐Álvarez, Triadó‐Margarit, Camarero, Casamayor, & Catalan, 2018; 33% Llorens‐Marès et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Environmental variation between sites was categorized using 16 variables known to impact zooplankton community composition (Hansson et al 2019). Twelve environmental variables were measured at each site: pH, dissolved oxygen, conductivity, temperature, maximum depth, water transparency, chlorophyll a, total phosphorus, total nitrogen, dissolved organic carbon, dissolved inorganic carbon, and colored dissolved organic matter (detailed sampling methods can be found in Appendix S1).…”
Section: Site Characterizationmentioning
confidence: 99%